2021
DOI: 10.1098/rspa.2020.0217
|View full text |Cite
|
Sign up to set email alerts
|

Observation and modelling of solar jets

Abstract: The solar atmosphere is full of complicated transients manifesting the reconfiguration of the solar magnetic field and plasma. Solar jets represent collimated, beam-like plasma ejections; they are ubiquitous in the solar atmosphere and important for our understanding of solar activities at different scales, the magnetic reconnection process, particle acceleration, coronal heating, solar wind acceleration, as well as other related phenomena. Recent high-spatio-temporal-resolution, wide-temperature coverage and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 336 publications
6
79
0
Order By: Relevance
“…Here, the narrow, quasi-periodic EUV wave train should be a so-called QFP magnetosonic wave like those reported in previous studies (e.g. Liu et al, 2011;Shen and Liu, 2012b;Shen et al, 2013a; Yuan et al, 2013;Miao et al, 2021). The propagation of such QFP waves is typically trapped in coronal loops acting as waveguides (high density, low Alfvén speed).…”
Section: Flare-ignited Quasi-periodic Euv Wave Trainssupporting
confidence: 60%
See 1 more Smart Citation
“…Here, the narrow, quasi-periodic EUV wave train should be a so-called QFP magnetosonic wave like those reported in previous studies (e.g. Liu et al, 2011;Shen and Liu, 2012b;Shen et al, 2013a; Yuan et al, 2013;Miao et al, 2021). The propagation of such QFP waves is typically trapped in coronal loops acting as waveguides (high density, low Alfvén speed).…”
Section: Flare-ignited Quasi-periodic Euv Wave Trainssupporting
confidence: 60%
“…It is worth pointing out that CMEs are not a necessary requirement for producing large-scale EUV waves, although they have been generally accepted as the driver of EUV waves. Some recent observations have shown that large-scale EUV waves can also be driven by various non-CME-associated solar eruptions, such as coronal jets (Zheng et al, 2013;Shen et al, 2018a,c,d;Shen, 2021), mini-filament eruptions (Wang et al, 2020), expanding coronal loops (Su et al, 2015;Shen et al, 2017bShen et al, , 2018c, and newly formed sigmoidal loops (Zheng et al, 2012b). Recently, large-scale quasi-periodic EUV waves with periods of a few minutes have been detected, which can propagate simultaneously along and across magnetic-field lines and cause the oscillations of filaments and coronal loops (Liu et al, 2012;Shen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the SDO was launched with two important instruments onboard: the Atmospheric Imaging Assembly (AIA: Lemen et al, 2012), providing extreme ultraviolet (EUV) and ultraviolet (UV) data, and the Helioseismic and Magnetic Imager (HMI: Scherrer et al, 2012), providing magnetograms both with a high spatial resolution (0.6 and 0.5 arc sec) and high temporal cadence (12 and 45 s). A very impressive number of publications concerning jets observed with AIA with more precise results of their characteristics and their triggers appeared (Raouafi et al, 2016;Shen, 2021). In the review of Hinode Review Team (2019), there is not only an interesting discussion of the jets observed with the Hinode instruments but also a deep discussion on the origin of the jets observed with the SDO/AIA.…”
Section: Sdo and The Onset Of Jetsmentioning
confidence: 99%
“…Jets may also be formed by shock waves (e.g., De Pontieu et al, 2004). Detailed descriptions of coronal jets can be found in recent reviews (Innes et al, 2016;Raouafi et al, 2016;Shen, 2021).…”
Section: Introductionmentioning
confidence: 99%